2011
DOI: 10.1007/s12034-011-0103-7
|View full text |Cite
|
Sign up to set email alerts
|

Electrical properties and scaling behaviour of Sm3 +  doped CaF2-bismuth borate glasses

Abstract: The electrical properties for 20Bi 2 O 3 -60B 2 O 3 (20−x)-CaF 2 -xSm 2 O 3 glasses (0 ≤ x ≤ 2) were measured in the temperature range 297 K up to 629 K and in the frequency range 0·1-100 kHz. The d.c. and a.c. conductivity values and the dielectric loss (tan δ) values were found to increase with increasing Sm 2 O 3 content, whereas the activation energy of conductivities and the dielectric constant decreased. These results were attributed to the introduction of the rare earth ions; promote the formation of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…At lower frequency the charge carriers may easily hop out of the low energy sites and thus accumulate at high energy barrier sites. 18,19 This results in an increased net polarization and hence leads to an increased dielectric constant and loss. However, at high frequency, the electric field changes so fast that the oscillations of charge carriers tend to lag behind the applied electric field.…”
Section: Resultsmentioning
confidence: 99%
“…At lower frequency the charge carriers may easily hop out of the low energy sites and thus accumulate at high energy barrier sites. 18,19 This results in an increased net polarization and hence leads to an increased dielectric constant and loss. However, at high frequency, the electric field changes so fast that the oscillations of charge carriers tend to lag behind the applied electric field.…”
Section: Resultsmentioning
confidence: 99%
“…And hence reduction in the polarization (due to the departure of charge, massing up at the free energy barrier) and reduction in the values of dielectric parameters. [47][48][49][50][51] At low frequencies, all the polarization mechanisms are active. Still, as the frequency increases to the higher value, polarization decreases because dipoles do not fit in with the varying external field, resulting in the reduction of dielectric relaxation parameters.…”
Section: Resultsmentioning
confidence: 99%
“…Sodium manganese oxide as a high-performance cathode was designed utilizing the complementary effects of inert Ti 4+ ions and active Ni 2+ ions . It has been reported that incorporation of rare-earth elements as network modifiers leads to the generation of more nonbridging oxygen (NBO) atoms in the glass network. This is an effective approach for achieving faster ion migration ensuring enhanced conductivity with reduced activation energy …”
Section: Introductionmentioning
confidence: 99%
“…38−40 This is an effective approach for achieving faster ion migration ensuring enhanced conductivity with reduced activation energy. 41 On the verge of miniaturization, the advent of nanoscale materials has provided several new developments in the field of next-generation batteries, 42,43 dielectric supercapacitors, 44−46 and magnetic sensors. 47−50 The reduced size in the nanomaterial scales down the ion diffusion length and accelerates ion transport.…”
Section: ■ Introductionmentioning
confidence: 99%